Engaging City Residents in Climate Action: Addressing the Personal and Group Value-Base Behind Residents' Climate Actions. (November 2020) - Bouman, Thijs; Steg, Linda
Cities can play a pivotal role in accelerating climate action, that is, climate mitigation and adaption. Yet, the success of cities' climate strategies strongly depends on the cities' residents, who often have to accept, adopt, undertake and participate in climate actions. This article discusses how a better understanding of city residents' motives—particularly the personal and group values that underlie their climate actions—could foster climate action in cities. Importantly, it engages with the rich literature in the social sciences on personal values, which—though typically overlooked by policymakers—highlights the relevance of focusing on personal biospheric values (i.e., caring about nature and the environment) in explaining and promoting residents' climate actions. Additionally, the article provides novel insights into how perceived biospheric group values (i.e., the extent to which relevant groups are perceived to endorse biospheric values) can strengthen the value-base for climate actions, particularly among those residents who weakly endorse biospheric values. Critically, it provides concrete examples of how cities can strengthen the group value-base for climate actions, thereby showing how cities can play a unique role in engaging residents in climate action.